IMPLEMENTATION OF LITERACY OF STUDENTS OF NAMIRA SMP, CITY OF PROBOLINGGO IN SUPPORTING THE LEARNING OF INDONESIAN LANGUAGE - Rozi, Muhammad Fathur (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
This study aims to describe the literacy of Namira Middle School students in Probolinggo City. The scope includes: (1) implementation of literacy activities for class VII students at SMP Namira Probolinggo City, (2) utilization of literacy for class VII students in supporting Indonesian language learning in class. This study uses a qualitative descriptive approach, the subjects of this research are students, especially class VII, and the object of this research is the literacy of Namira Middle School students, Probolinggo City. Existing data in this study using the method of observation, interviews, and documentation. The results of this study describe: (1) the implementation of literacy activities for class VII students of Namira Middle School, Probolinggo City. The implementation of student literacy at school is quite smooth which is carried out on Tuesdays and Thursdays in particular. On the other hand, researchers correlate it with The Big Six theory, (2) the use of literacy in class VII students in supporting Indonesian language learning in class. The favorite reading books for students are literature books. In this case, students have taken advantage of literacy by learning in class, especially Indonesian language material.